Influence of the dominant thinking style in the degree of novelty of designs in virtual and traditional working environments. Issue 7 (2nd July 2016) - Mulet, Elena; Chulvi, Vicente; Royo, Marta; Galán, Julia
ABSTRACT: One's thinking and reasoning style defines individual preferences when interacting and communicating with others. This work aims to analyse whether the thinking and reasoning style of the design teams exerts an influence on the degree of novelty of the design outcomes in two working environments: a face-to-face environment and a virtual environment. To address this, an experiment was set up in which 21 teams, each made up of 3 design students, were asked to obtain new solutions to 2 design problems, one of them in a face-to-face environment and the other in a virtual environment. The teams were defined according to their thinking and reasoning style, and the novelty of the design outcomes was measured with the SAPPhIRE model of causality. The results show that, overall, the degree of novelty is very similar in both environments, although it is a little higher in virtual environments. Teams with a rational style produce more novel results when using information and communication technologies than in a face-to-face environment. Teams with an interpersonal style, on the other hand, generate the least novel solutions when using technologies and produce the most novel solutions when they work in a face-to-face environment.